Mucolipidosis Type II Affecting 1 Fetus and Placental Disk of a Dichorionic-Diamnionic Twin Gestation: A Case Report and Review of the Literature. (July 2019) - Chapel, David B.; Choy, Bonnie; Pytel, Peter; Husain, Aliya N.; Lastra, Ricardo R.
Abstract : Mucolipidosis type II, also known as I-cell disease, is an autosomal recessive inborn error of metabolism, resulting from loss-of-function mutations in GNPTAB . Affected infants exhibit multiple physical anomalies and developmental delay, and death from disease follows in early childhood. Here we present an instructive case of mucolipidosis type II affecting 1 fetus and placental disk in a dichorionic-diamnionic twin pregnancy delivered at 36-wk gestation. The second twin and placental disk showed no abnormality. On microscopic examination, the affected placenta displayed marked vacuolization of the syncytiotrophoblast and Hofbauer cells, which was confirmed on ultrastructural examination. To our knowledge, this is the first description of placental findings in a twin pregnancy, wherein only 1 twin is affected by an inborn error of metabolism. This provides an opportunity to highlight the placental abnormalities seen in this group of diseases, and to emphasize the role of pathologic examination in early detection of otherwise unsuspected inborn errors of metabolism.